Efektivitas Kebijakan Penataan Parkir terhadap Pengurangan Kemacetan dan Peningkatan Ketertiban Ruang Publik (Studi Kasus Royal Kawasan Baroe Kota Serang) - Ajeng Pratiwi; Satrio Tri Buwono; Suci Patmawati; Nur Rochmah Subchiyah; Zulfan Aghnia; Reza Damayanti (INDO PUBLISHING, 2026)
Parking management policies improve public order and reduce traffic congestion in the Royal Baroe area of Serang City. Unregulated parking and widespread illegal parking have caused many adverse effects, including narrowing roadways, obstructing traffic, and disrupting the function of public spaces. This study is a qualitative case study. Data were collected through field observations, interviews with parking attendants, business owners, road users, and the Serang City Transportation Department, as well as documentation regarding parking management policies. The results indicate that parking management policies in the Royal Baroe area have improved public space order and reduced traffic congestion levels. Traffic has become more orderly thanks to parking lot management, the installation of traffic signs, and supervision by officers. However, the policy is not yet fully effective due to a lack of public awareness and a very limited number of officers in the field. Therefore, for the policy to succeed, collaboration between the community and coordination among agencies are necessary.